Effect of Fun Learning Enrichment Program (FLEP) on At-Risk Students’ Motivation and Aspiration to Learn - Noriah Mohd Ishak; Melor Md Yunos; Salleh Amat; Abu Yazid Abu Bakar; Mhd Subhan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The purpose of this study is to examine effects of the Fun Learning Enrichment Program (FLEP) on motivation and aspiration to learn among population of low-achieving students. The study used quasi experimental design with pre-post control group. A total of 596 students participated in the study for three consecutive years. The students were given a module consisted of 120 fun learning enrichment activities in mathematics and science that promotes self-motivation and aspiration to learn. Results show significant increase in motivation and aspiration to learn among the students after attending the FLEP program. In conclusion, low-achieving students can develop motivation and aspiration to learn when given environment that promotes positive learning experience.